O papel dos exames complementares na confirmação diagnóstica e no diagnóstico diferencial das síndromes demenciais - Moraes, Fabiano Moulin de [UNIFESP] (2016)
Objectives: To evaluate the role of supplementary exams (TSH, B12, VDRL, HIV, Brain CT or MRI, depression scale and when appropriate SPECT, Polysomnography, cerebrospinal fluid and electroencephalogram) on the final diagnostic confirmation and on the differential diagnosis in dementia syndromes after at least one year follow up. Methods: A retrospective observational study to estimate the contribution of the supplementary exams on the final diagnosis of the dementia syndromes established after the initial diagnosis. The collected data were sociodemographic, types of the patient and family complaints, family history, comorbidities, disability scale measured by the Clinical Dementia Rating (CDR), neurological physical examination, neuropsychological tests divided in cognitive domains and finally the results of the supplementary exams including a depression scale (geriatric depression scale ?GDS). Once an initial diagnosis was made, it was compared with the final diagnosis to asses which exams had any relevant impact in the stability or change whether degenerative or reversible syndromes. Besides the exams, the other clinical variables were evaluated to check for any relevant influence on the final diagnosis. Results: There were selected 432 patients from 1485 patients from a single university center. From this sample, 110 (25,4 %) patients have their diagnosis changed, most of them adding the vascular component to initial diagnosis as a significant contribution to the dementia syndrome. The clinical variables related to the diagnostic stability was the presence symmetric parkinsonism in neurological examination, initial diagnosis of vascular dementia, the presence of diabetes and systemic arterial hypertension, the presence of long term memory deficit in the neuropsychological evaluation and normal neuroimaging (brain CT or MRI). Regarding the reversibility of dementia, depression was the most important mimicker, responsible for 13 from the 16 patients (3,7% of the total sample) who had their severity reduced. The other three patients had normal pressure hydrocephalus (NPH) treated surgically. The clinical variables related to reversibility were follow up time, absence of the family complaint, sedentary, initial diagnosis of NPH, initial diagnosis of depression and normal brain image(CT or MRI). Conclusion: Regarding the supplementary exams, only the depression screening scale and the brain image were statistically relevant for the differential diagnosis of the dementia syndromes. Furthermore, every step of the clinical diagnosis including history, comorbidities, physical examination and neuropsychological battery were relevant as well.